Informal Economy and Employment in Albania - Sino, Lediona (Richtmann Publishing, 2012)
It’s clearly to say that, informal economy is one of the most subjects that have impact in the growth of the country’s economy.Discussing about the informal economy, can say that this is a current issue not only for Albania, but also for all those countries intransition. In this paper is intended to analyze: What is the size of informal economy and informal employment (black labor) by sectors,gender, ages and regions in Albania? What is the impact of informal economy in Albanian’s growth? Nowadays an important subject isthe black labor. The method of regression analysis is used to shed further light on this informal sector’s data. The study of this paper isrealized on the basis of analysis the impact of informality on the GDP growth. From this analysis can draw conclusions about the sectorwith the highest level of informality, and it cause a negative impact on the development of economy. Appropriate measurement istherefore of high importance to analyze and design of appropriate strategies to reduce informality. Answering the questions, results aclearly picture about the economic environment of Albania and the things that must to do in order to resolve some of the economicproblems.